Astragalin: a food-origin flavonoid with therapeutic effect for multiple diseases - Chen, Junren; Zhong, Kexin; Qin, Siqi; Jing, Yiqi; Liu, Shengmeng; Li, Dan; Peng, Cheng (Frontiers in Pharmacology, 2023)
Naturally occurring flavonoids have long been utilized as essential templates for the development of novel drugs and as critical ingredients for functional foods. Astragalin (AG) is a natural flavonoid that can be isolated from a variety of familiar edible plants, such as the seeds of green tea, Morus alba L., and Cuscuta chinensis. It is noteworthy that AG has a wide range of pharmacological activities and possesses therapeutic effects against a variety of diseases, covering cancers, osteoarthritis, osteoporosis, ulcerative colitis, mastitis, obesity, diabetes mellitus, diabetic complications, ischemia/reperfusion injury, neuropathy, respiratory diseases, and reproductive system diseases. This paper reviewed the natural resource and pharmacokinetics of AG, and systematically summarized the pharmacological activities and potential mechanisms of AG in treating diverse diseases, in order to promote the development of AG as a functional food and providing references for its clinical application in diseases therapy.